Beneficial Role of Carica papaya Extracts and Phytochemicals on Oxidative Stress and Related Diseases: A Mini Review - Kong, Yew Rong (Biology (Basel), 2021)
SIMPLE SUMMARY: This review highlights the medicinal benefits of a natural remedy, the Carica papaya extracts and its phytochemicals. In this review, the potential of Carica papaya against various conditions, including cancer, inflammation, aging, healing of the skin, and lifelong diseases has been summarized and discussed. In short, more research and development should focus on this natural remedy that can potentially act as a prophylaxis against chronic diseases. ABSTRACT: Oxidative stress is a result of disruption in the balance between antioxidants and pro-oxidants in which subsequently impacting on redox signaling, causing cell and tissue damages. It leads to a range of medical conditions including inflammation, skin aging, impaired wound healing, chronic diseases and cancers but these conditions can be managed properly with the aid of antioxidants. This review features various studies to provide an overview on how Carica papaya help counteract oxidative stress via various mechanisms of action closely related to its antioxidant properties and eventually improving the management of various oxidative stress-related health conditions. Carica papaya is a topical plant species discovered to contain high amounts of natural antioxidants that can usually be found in their leaves, fruits and seeds. It contains various chemical compounds demonstrate significant antioxidant properties including caffeic acid, myricetin, rutin, quercetin, α-tocopherol, papain, benzyl isothiocyanate (BiTC), and kaempferol. Therefore, it can counteract pro-oxidants via a number of signaling pathways that either promote the expression of antioxidant enzymes or reduce ROS production. These signaling pathways activate the antioxidant defense mechanisms that protect the body against both intrinsic and extrinsic oxidative stress. To conclude, Carica papaya can be incorporated into medications or supplements to help manage the health conditions driven by oxidative stress and further studies are needed to investigate the potential of its chemical components to manage various chronic diseases.